Center of mass estimation in the V2-technique using a single IMU-setup - Gløersen, Ø.; Myklebust, H.; Dysthe, D. K.; Hallén, J. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: The dynamics of an athlete's center of mass (COM) is central for calculating external work and energy fluctuations (Kehler et al. 2014). However, accurate measurements of COM dynamics are usually restricted to a laboratory environment. To investigate the possibility for simple COM measurements in field, a Sacrum model (SM) has been proposed for ski skating (Myklebust et al. 2013). However, results were satisfactory only in the medio-lateral direction. Here we augment SM with measurements of pelvis orientation in addition to translation. Our hypothesis is that such a model can be used to predict COM displacement also in the sagittal plane.